Effectiveness of mindfulness-based audio-visual interventions on self-efficacy in childbirth readiness among high-risk pregnant women - Aisyah Nur Fitri; Misrawati, Misrawati; Erika, Erika; Hasan, Haliza (The Journal of Palembang Nursing Studies, 2025)
Background: High-risk pregnancies in women under 20 or over 35 years are commonly associated with low self-efficacy, leading to anxiety, poor coping, and inadequate childbirth readiness. Few studies have targeted interventions to directly improve self-efficacy, and mindfulness delivered through audiovisual media represents a promising yet underutilized approach to enhance psychological preparedness in this population. Objective: To evaluate the effectiveness of an audiovisual mindfulness intervention on self-efficacy in high-risk pregnant women preparing for childbirth. Methods: A quasi-experimental pre-test–post-test control group design was conducted among 66 third-trimester pregnant women, purposively assigned to experimental (n = 33) and control (n = 33) groups. The intervention was delivered via the MIESRA application, providing audiovisual mindfulness exercises to promote maternal–fetal bonding and psychological well-being. The experimental group received three 15-minute sessions over seven days, while the control group received standard antenatal care. Self-efficacy was measured using a validated scale and analyzed with Wilcoxon, dependent t-test, and independent t-test.  Results: The mean self-efficacy score in the experimental group increased from 63.36 (SD = 5.18) to 67.82 (SD = 3.93), while the control group showed only a slight increase from 64.33 (SD = 6.44) to 64.55 (SD = 6.14). Statistical analysis confirmed a significant improvement in the experimental group compared with controls (p = 0.012). Participants receiving mindfulness reported feeling calmer, more confident, and better prepared for childbirth. Conclusion: Audiovisual mindfulness intervention effectively improved self-efficacy among high-risk pregnant women. Integrating such tools into antenatal care may empower vulnerable mothers, foster resilience, and enhance psychological readiness for childbirth.